Evaluation of canine tympanic membrane integrity using positive contrast computed tomography canalography - Alves-Nores, V.; Plested, M. J.; Rubial, R.; Salgüero, R. (Frontiers in Veterinary Science, 2024)
Introduction The assessment of the integrity of the tympanic membrane (TM) can be a diagnostic challenge in patients with otitis externa and/or otitis media (OM) under an otoscopic examination. In computed tomography (CT), the TM is not always visualized. However, a positive contrast canalography using conventional radiography has been previously described to evaluate the TM integrity. Objective This single-center study aimed to describe the positive contrast canalography technique in CT and its usefulness in identifying TM integrity in 11 dogs. Methods Dogs with clinical signs of ear disease underwent CT canalography following a systematic protocol. Result The presence of contrast medium and contrast homogeneity within the tympanic cavity was assessed, confirming TM rupture when contrast medium was present in the tympanic cavity. CT canalography was performed in 16 ears, and in 7 of the 16 ears (44%), there was a contrast in the tympanic cavity, confirming TM rupture (positive CT canalography result). In two of the seven cases (29%), rupture of the TM was identified in both otoscopic and CT canalography. In the remaining five of the seven (71%) positive CT canalography results, tympanic membrane rupture was identified only by CT canalography. Discussion In conclusion, a positive contrast CT canalography is a complementary and safe technique to assess TM integrity, with a potentially higher sensitivity than otoscopic examination for the diagnosis of TM rupture in dogs.